Partisipasi Anggota Kelompok dalam Pengolahan dan Pemasaran Loloh Cemcem di Desa Wisata Penglipuran, Kabupaten Bangli, Provinsi Bali - SILITONGA, CORNELLA FEBRINAULY; SURYAWARDANI, IGA. OKA; DIARTA, I KETUT SURYA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.4, Oktober 2019, 2019)
Participation of Group Members in Processing and Marketing of Loloh Cemcem in Penglipuran Tourism Village, Bangli Regency, Bali Province. Group participation in creating and developing local village food products is useful for maintaining the sustainability of local products and creating new jobs. Loloh CemcemProduction Group of Penglipuran is one of groups that develops local village food products that have the potential to be developed and is able to create jobs. However, efforts in developing local products and increasing this group are also related to group membership that has relations in production, so that the group participation is expected to be able to overcome the obstacles faced. The purpose of this study was to determine the level of participation of group members in processing and marketing. The research location took place in Penglipuran Tourism Village, Bangli Sub-District, Bangli Regency. The analytical method used was descriptive statistical analysis.The results showed that the participation of group members in processing of Loloh Cemcem was classified in the high category with a score of 69.72% with detailed indicators of decision making included reaching a score of 66.78%, implementation indicators reaching a score of 71.56%, the evaluation indicator reached a score of 59.58%, and the indicator of enjoying the results reached a score of 75.15%. The level of participation of group members in the Loloh Cemcem marketing was in the low category with a score of 58.51% with details on the decision-making indicators reaching a score of 55.93%, the implementation indicator classified reached a score of 49.37%. The evaluation indicators reached a score of 60%, and the indicator of enjoying the results reached with a score of 68.75%.The suggestion that can be given to the group is that the participation of members in the group must be increased especially in loloh members are expected to be more courageous in conveying ideas and suggestions in groups.